Solidarity across cyberspace: Internet campaigning, labour activism and the remaking of trade union internationalism. (1st April 2008) - Bruce Robinson,
Abstract : Global communication through the Internet has provided new possibilities for trade union solidarity action across national boundaries. Email campaigns are one form of this. Taking the example of an email campaign in support of imprisoned Eritrean trade unionists, this paper examines the social organisation and information flows underlying such campaigns. These throw light on the effectiveness of such actions, their capacity to overcome inequalities in access to ICTs and current debates on the role of the Internet in the remaking of trade union internationalism managing to develop a certain social power.